Designing metal framework partial denture: Mendesain gigi tiruan sebagian kerangka logam - Mariska Juanita; Eri Hendra Jubhari (Makassar Dental Journal, 2021)
The number of partiallyedentulous adults is increasing, and many patients will require replacement of missing teeth. Although current treatment options also include fixed partial dentures and implants, removable partial dentures (RPDs) can have advant-ages and are widely used in clinical practice. However, a significant need exists to advance materials and fabrication technologies because of the unwanted health consequences associated with current RPDs. The RPDs consists of many components, such as major and minor connector, direct and indirect retainer, also rests. The variety of anatomic considerations related to oral con-ditions may affect selection of these components. The objective of this review is to discuss data related to RPDs design and factors affecting its selection. It was concluded that prosthodontists need to fully understand the basic of RPDs design princi-ples and should be familiar with those structures.